Coping mechanisms of cancerous child’s mother: A field stady in Annaba - Boucenna, Abdelouafi Zouhir; Boudjeriou, Narimene (Journal of Human Sciences, 2022)
The aim of this study was to identify the degree of perceived stress that the mother of the cancerous child is suffering from, and the nature of the coping strategies she uses to cope with it. we opted for the clinical method with the case of our study as a technique, using the semi-directive interview and the Levinstein test (PSI) and the Endler and Parker test (CISS) with our case. The study was conducted at the SAINT THERESE Annaba pediatric clinic. This study got to the following results: The mother of the cancerous child suffers from a very high degree of perceived stress and feels helpless against of her child’s illness. The mother of the cancerous child uses different and varied coping strategies to cope with stressful situations, and she more or less exclusively uses some sort of strategy that reflects her internal and external resources.